FACE THE FEAR OF FALLING BEHIND IN THE DIGITAL AGE: RECOGNIZING AND OVERCOING FOMO - Mika Melliani; Ribka Wahyu Christian, Pilenia, Lela Oktaria, Daniel Np Simatupang, Enjelia, Yola Pradita; Yesyurun Munthe (Indonesian Journal of Education (INJOE), 2024)
This article looks at the "Fear of Missing Out," or "FOMO," issue in the turbulent digital age. As societal norms change to emphasize reliance on digital devices and social media, FOMO is becoming a more commonplace issue in day-to-day living. This study explores the psychological effects of FOMO on mental health, looks into its underlying roots, and offers practical methods for dealing with and overcoming this fear. We show using an analytical method that FOMO can result in tension, worry, and feelings of inferiority. This diary contains ideas for increasing offline social connectedness, increasing self-awareness, and managing time wisely. Consequently, this study offers a comprehensive perspective on how people might more sensibly traverse the digital age while maintaining their psychological.